Impact of improved observed hand hygiene on bloodstream infection rates in Ireland. A prospective segmented regression analysis, 2009–2016. (2020) - Smiddy, M.P.; Murphy, O.M.; Savage, E.; Fitzgerald, A.P.; FitzGerald, S.; Browne, J.
Abstract: Participation in European surveillance for bloodstream infection (BSI) commenced in Ireland in 1999 with all laboratories ( n = 39) participating by 2014. Observational hand hygiene auditing (OHHA) was implemented in 2011. The aim of this study was to evaluate the impact of OHHA on hand hygiene compliance, alcohol hand rub (AHR) procurement and the incidence of sensitive and resistant Staphylococcus aureus and Enterococcus faecium and faecalis BSI. A prospective segmented regression analysis was performed to determine the temporal association between OHHA and outcomes. Observed hand hygiene improved from 74.7% (73.7–75.6) in 2011 to 90.8% (90.1–91.3) in 2016. AHR procurement increased from 20.1 l/1000 bed days used (BDU) in 2009 to 33.2 l/1000 BDU in 2016. A pre-intervention reduction of 2% per quarter in the ratio of methicillin sensitive Staphylococcus aureus BSI/BDU stabilized in the time period after the intervention ( P < 0.01). The ratio of Methicillin resistant Staphylococcus aureus (MRSA) BSI/BDU was decreasing by 5% per quarter pre-intervention, this slowed to 2% per quarter post intervention, ( P < 0.01). There was no significant change in the ratio of vancomycin sensitive ( P = 0.49) or vancomycin resistant ( P = 0.90) Enterococcus sp. BSI/BDU post intervention. This study shows national OHHA increased observed hand hygiene compliance and AHR procurement, however there was no associated reduction in BSI.